(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
This research aims to outline a historical overview of vocational education and labor training for the clothing industry in the cities such as Blumenau, Brusque and Jaraguá do Sul. The bibliographical and documentary research presents a timeline between 1850 and 2004, that covers the period between the beginning of Santa Catarina northeast colonization and the consolidation of fashion higher education in the mentioned cities. The study presents the informal training of apprentices such as tailors and domestic seamstresses, public policies aimed at professional training, and above all, the constitution of professional training in the clothing industry organized by the Federação das Indústrias do Estado de Santa Catarina (FIESC) and the “S” System, following the demands of the industrial development in the State. In face of industrialization, the tailoring craft has lost its social function, but its methods of modeling, cutting, and sewing clothes have grown and multiplied in didactic courseware, and in the teaching and learning processes that enable students and teachers. It is understood that the professionalizing educational system must encompass intellectual development, professional qualification and citizenship education. Education cannot just be limited to finding solutions for labor demands, but rather be an active force of building this world, striving for humanization in the teaching and learning processes, so that it is helps in the political, economic, social and professional context.